Impact of Sacubitril/Valsartan on surfactant binding proteins, central sleep apneas, lung function tests and heart failure biomarkers: Hemodynamic or pleiotropism? - Mapelli, Massimo; Mattavelli, Irene; Salvioni, Elisabetta; Banfi, Cristina; Ghilardi, Stefania; De Martino, Fabiana; Gugliandolo, Paola; Mantegazza, Valentina; Volpato, Valentina; Basile, Christian; Branco Pires, Maria Inês Fiuza; Sassi, Valentina; et al. (Frontiers in Cardiovascular Medicine, 2022)
Purpose Little is known about the mechanism underlying Sacubitril/Valsartan effects in patients with heart failure (HFrEF). Aim of the study is to assess hemodynamic vs. non-hemodynamic Sacubitril/Valsartan effects by analyzing several biological and functional parameters. Methods Seventy-nine patients (86% males, age 66 ± 10 years) were enrolled. At baseline and 6 months after reaching the maximum Sacubitril/Valsartan tolerated dose, we assessed biomarkers, transthoracic echocardiography, polysomnography, spirometry, and carbon monoxide diffusing capacity of the lung (DLCO). Results Mean follow-up was 8.7 ± 1.4 months with 83% of patients reaching Sacubitril/Valsartan maximum dose (97/103 mg b.i.d). Significant improvements were observed in cardiac performance and biomarkers: left ventricular ejection fraction increased (31 ± 5 vs. 37 ± 9 %; p < 0.001), end-diastolic and end-systolic volumes decreased; NT-proBNP decreased (1,196 [IQR 648–2891] vs. 958 [IQR 424-1,663] pg/ml; p < 0.001) in parallel with interleukin ST-2 (28.4 [IQR 19.4–36.6] vs. 20.4 [IQR 15.1–29.2] ng/ml; p < 0.001) and circulating surfactant binding proteins (proSP-B: 58.43 [IQR 40.42–84.23] vs. 50.36 [IQR 37.16–69.54] AU; p = 0.014 and SP-D: 102.17 [IQR 62.85–175.34] vs. 77.64 [IQR 53.55-144.70] AU; p < 0.001). Forced expiratory volume in 1 second and forced vital capacity improved. DLCO increased in the patients' subgroup (n = 39) with impaired baseline values (from 65.3 ± 10.8 to 70.3 ± 15.9 %predicted; p = 0.013). We also observed a significant reduction in central sleep apneas (CSA). Conclusion Sacubitril/Valsartan effects share a double pathway: hemodynamic and systemic. The first is evidenced by NT-proBNP, proSP-B, lung mechanics, and CSA improvement. The latter is confirmed by an amelioration of DLCO, ST-2, SP-D as well as by reverse remodeling echocardiographic parameters.